Factors Influencing Auditor Switching: Insights from Audit Opinion, Audit Delay, and ROA - Agusta Amanda Wulandari; Rosjelin Runesi (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This research aims to measure the impact of audit opinion, audit delay, and Return on Assets (ROA) on auditor switching in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This study is a descriptive quantitative research. The data in this study were obtained from secondary data of annual financial reports of manufacturing companies for the period of 2019-2023. The population in this study consists of 173 manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. The sample in this research consists of companies selected based on certain criteria. The data analysis techniques used are descriptive statistics and logistic regression analysis, using SPSS 25 software. The results of this study show that audit opinion and Return on Assets (ROA) do not partially affect auditor switching, while audit delay has a positive effect on auditor switching.